Fundamental study and analysis of CAT5e cable for NEXT and ELFEXT - Handy, Ali Munir; Nordin, Saad, Assoc. Prof. Dr.; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Ahmad Mujahid, Ahmad Zaidi, Dr.; Mohd Zuki, Yusoff, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org